Higher Emergency Physician Chest Pain Hospitalization Rates Do Not Lead to Improved Patient Outcomes. Issue 1 (January 2021) - Natsui, Shaw; Sun, Benjamin C.; Shen, Ernest; Redberg, Rita F.; Ferencik, Maros; Lee, Ming-Sum; Musigdilok, Visanee; Wu, Yi-Lin; Zheng, Chengyi; Kawatkar, Aniket A.; Sharp, Adam L.
Abstract : Background: Wide variation exists for hospital admission rates for the evaluation of possible acute coronary syndrome, but there are limited data on physician-level variation. Our aim is to describe physicians' rates of admission for suspected acute coronary syndrome and associated 30-day major adverse events. Methods: We conducted a retrospective analysis of adult emergency department chest pain encounters from January 2016 to December 2017 across 15 community emergency departments within an integrated health system in Southern California. The unit of analysis was the Emergency physician. The primary outcome was the proportion of patients admitted/observed in the hospital. Secondary analysis described the 30-day incidence of death or acute myocardial infarction. Results: Thirty-eight thousand seven hundred seventy-eight patients encounters were included among 327 managing physicians. The median number of encounters per physician was 123 (interquartile range, 82–157) with an overall admission/observation rate of 14.0%. Wide variation in individual physician admission rates were observed (unadjusted, 1.5%–68.9%) and persisted after case-mix adjustments (adjusted, 5.5%–27.8%). More clinical experience was associated with a higher likelihood of hospital care. There was no difference in 30-day death or acute myocardial infarction between high- and low-admitting physician quartiles (unadjusted, 1.70% versus 0.82% and adjusted, 1.33% versus 1.29%). Conclusions: Wide variation persists in physician-level admission rates for emergency department chest pain evaluation, even in a well-integrated health system. There was no associated benefit in 30-day death or acute myocardial infarction for patients evaluated by high-admitting physicians. This suggests an additional opportunity to investigate the safe reduction of physician-level variation in the use of hospital care. Abstract : Supplemental Digital Content is available in the text.